The Changing role of Sound-Symbolism for small versus large vocabularies - Brand, James; Monaghan, Padraic; Walker, Peter * (Wiley Commercial Publisher for Cognitive Science Society, 2017)
Natural language contains many examples of sound-symbolism, where the form of the word carries information about its meaning. Such systematicity is more prevalent in the words children acquire first, but arbitrariness dominates during later vocabulary development. Furthermore, systematicity appears to promote learning category distinctions, which may become more important as the vocabulary grows. In this study, we tested the relative costs and benefits of sound symbolism for word learning as vocabulary size varies. Participants learned form meaning mappings for words which were either congruent or incongruent with regard to sound-symbolic relations. For the smaller vocabulary, sound-symbolism facilitated learning individual words, whereas for larger vocabularies sounds-symbolism supported learning category distinctions. The changing properties of form-meaning mappings according to vocabulary size may reflect the different ways in which language is learned at different stages of development.